SENI PARTISIPASI DI KAMPUNG KREATIF DAGO POJOK BANDUNG - Ardi Radiansyah; Wanda Listiani; Zaenudin Ramli (ATRAT: Jurnal Seni Rupa, 2020)
This research describes how the concept of participation and the practice of participatory art affect Dago Pojok community’s creative awareness in forming a creative village. Through a descriptive method and qualitative approach were used in the study, it collected qualitative data taken from interviews, observations and documentation studies. Throughout 11 (eleven) informants that participated to provide detailed information about community participation in forming the creative village, the results show that community involvement in shaping the idea of a creative village has resulted in a tradition-based creative village. Passive or active community involvement in the practices of participatory art has  impacts on the emergence of good relations between communities, the growth of creative awareness, the development of traditional arts and self-development that eventually lead to increase the economic level of Dago Pojok community. Based on the results of the study, the researchers suggested that they should develop innovation and creativity in the village to improve image of the creative village as a tourism village which offers special programs that are different from those of other villages.Keywords: Participation, Participatory Art, Creative Village, Dago Pojok________________________________________________________________ Penelitian ini mendeskripsikan bagaimana konsep partisipasi dalam praktik seni berdampak pada kesadaran kreatif masyarakat Dago Pojok sehingga membentuk kampung kreatif. Dengan menggunakan metode deskriptif dan pendekatan kualitatif, data yang dihasilkan diambil dari hasil wawancara, observasi dan studi dokumentasi. Melalui 11 (sebelas) orang yang dianggap dapat memberikan informasi terperinci mengenai partisipasi masyarakat dalam membentuk kampung kreatif, hasil yang didapat menunjukan bahwa keterlibatan masyarakat dalam membentuk gagasan kampung kreatif menghasilkan kampung kreatif berbasis tradisi. Keterlibatan masyarakat secara aktif dan pasif dalam praktik seni partisipasi berdampak pada timbulnya hubungan baik antar masyarakat, tumbuhnya kesadaran kreatif, berkembangnya seni tradisi dan pengembangan diri yang berdampak pada meningkatnya tingkat perekonomian masyarakat Dago Pojok. Berdasarkan hasil penelitian, saran yang diberikan adalah pengembangan inovasi dan kreativitas masyarakat di kampung kreatif yang bertujuan untuk meningkatkan citra kampung kreatif sebagai destinasi wisata yang memiliki program-program unggulan berbeda dengan kampung lainnya.Kata Kunci: Partisipasi, Seni Partisipatori, Kampung Kreatif, Dago Pojok